NURSING PRACTICE IN THE INSERTION AND MAINTENANCE OF THE PERCUTANEOUS CATHETER IN NEONATES OF A PUBLIC HOSPITAL, CALLAO, 2010-2015 - Chulle LLenque, Cecilia Maura (2020)
Objective: To analyze the nursing practice in the insertion and maintenance of the peripherally inserted central catheter (PICC) in newborns (RN) hospitalized in the Neonatal Intensive Care Unit during the years 2010 to 2015, in a hospital Callao, Peru. Material and methods: Descriptive and retrospective study. The technique of documentary analysis of the medical records and records was used, using an instrument that registered sociodemographic and clinical variables of the newborns to whom the PICC was placed in the period studied. The population consisted of 502 RN to which 625 catheters were inserted. The study was approved by the Institutional Research Ethics Committee. Results: 52.6% were males, 47.4% were 28 to 32 weeks of gestational age, 70.3% were premature infants with Hyaline Membrane Disease. 61.8% required the PICC for the administration of parenteral nutrition and 22.4% for antbiotic therapy. In 52.6%, insertion was achieved on the first attempt, the PICC was installed in the cephalic (35.8%) and basilic veins (21.4%). 47.2% had no complications during catheter insertion, 34.4% had bleeding. 88.9% of the NBs did not present complications during the PICC stay and 4.5% withdrew due to extravasation and phlebitis. Conclusions: Low complication rates are reported in the insertion and maintenance of the PICC in the RN due to the expertise of the neonatal ICU nurses.